2021
DOI: 10.1007/s10792-021-01977-w
|View full text |Cite
|
Sign up to set email alerts
|

Impact of failed ab-interno trabeculectomy (trabectome) on subsequent XEN45 gel stent implantation in pseudophakic eyes

Abstract: Purpose To determine the impact of failed ab-interno trabeculectomy on the postoperative outcome of subsequent XEN45 gel stent (Allergan, CA, USA) implantation in pseudophakic eyes. Methods In this retrospective single-center study, we included 60 pseudophakic eyes from 60 participants who underwent XEN45 gel stent implantation. Thirty eyes each underwent primary stent implantation (control group) or had previously undergone a failed ab-interno trabeculect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…With regard to previous MIGS, a publication about the impact of prior Trabectome® surgery on the outcome of XEN® by Kiessling et al provides a first more differentiated analysis [54]. Even though they included eyes with exfoliative glaucoma in addition to POAG, this study is more comparable to ours.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…With regard to previous MIGS, a publication about the impact of prior Trabectome® surgery on the outcome of XEN® by Kiessling et al provides a first more differentiated analysis [54]. Even though they included eyes with exfoliative glaucoma in addition to POAG, this study is more comparable to ours.…”
Section: Discussionmentioning
confidence: 57%
“…In total, 42% of their patients underwent an open conjunctival revision surgery and 12% needed a repeated surgery. As conclusion, Kiessling et al stated that a failed Trabectome® surgery does not affect the postoperative IOP, medication score, revision rate, repeated surgery rate, and success rate of a subsequent XEN® gel implantation [54].…”
Section: Discussionmentioning
confidence: 93%
“…In this case series of XEN ® -45 implantation, a majority of 72% (18/25) previously underwent Trabectome ® surgery. Kiessling et al have shown that trabeculectomy ab interno with the Trabectome ® does not interfere with following XEN ® -45 implantation in non-uveitic pseudophakic eyes [ 13 ]. Our case series is too small to prove a difference between eyes with or without previous Trabectome ® surgery.…”
Section: Discussionmentioning
confidence: 99%